Expression of prostaglandin E2 prostanoid receptor EP2 and interleukin-1βin laryngeal carcinoma – preliminary study - Mochocki, Marcin; Morawski, Piotr; Kopta, Renata; Brzezińska-Błaszczyk, Ewa; Stasikowska, Olga; Lewy-Trenda, Iwona; Circle, Student Scientific; Starska, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Expression of EP2 protein, the prostaglandin E 2 (PGE 2 ) receptor, produced by tumour microenvironment inflammatory cells as well as tumour cells, may promote cellular proliferation and growth in an autocrine and paracrine fashion. The phenomenon involving these proteins is regulated by interleukin 1β(IL-1). Many researchers indicate a connection of EP2 and IL-1βin various types of neoplasms with higher tumour progression and poor prognosis. The aim of this study was to analyse the EP2 expression within laryngeal carcinoma tissue and IL-1βlevels in peripheral blood mononuclear cell supernatants and to find relationships between clinicomorphological features. Material and methods : A group of 50 patients with verified squamous cell laryngeal carcinoma was analysed in this study. The pathological evaluation included pTNM depth of invasion according to tumour front grading criteria. Immunohistochemical analysis for membranous staining of EP2 in tumour tissues was used. The IL-1expression was determined by enzyme-linked immunosorbent assay (ELISA). Results : Increased EP2 expression in carcinoma cells was confirmed for more advanced tumours (pT3-pT4 vs. pT1-pT2, p < 0.0001 and pN1-3 vs. pN0, p = 0.02). Tumours with the highest aggressiveness identified by deeper invasion of submucosa or cartilage were characterised by the highest expression of EP2 (p < 0.0001). In laryngeal carcinomas characterised by a lower differentiation the highest EP2 expression in tumour cells was noted (p = 0.009). A positive relationship between IL-1βexpression and the presence of lymph node metastases was also confirmed (p = 0.04). Conclusions : The study indicates the potential effect of EP2 receptor and IL-1βon tumour progression in laryngeal carcinoma.